Congenital transmesenteric internal hernia; A rare cause of bowel ischemia in adults: A case report - Hasnaoui, Hamza; Mouaqit, Ouadii; Beillahi, Mohamed Lemine; Bouhaddouti, Hicham El; Benjelloun, El Bachir; Ousadden, Abdelmalek; Taleb, Khalid Ait (Journal of Surgery and Medicine, 2019)
Congenital transmesenteric hernias represent a very small group of internal hernias which are uncommon and are a rare cause of bowel obstruction and bowel ischemia in adults with few reported cases in published literature. Preoperative diagnosis of the condition is difficult, early intervention and surgical correction goes a long way in preventing high morbidity and mortality associated with cases of internal hernia. We present a case of true congenital transmesenteric hernia in a 31-year-old woman with no previous surgical history or trauma who presented with history of severe abdominal pain and the cessation of both feces and flatus. The abdominal CT scan could not confirm the diagnosis. The patient was operated upon on account of increasing abdominal pain and distention associated with shock. An exploratory laparotomy revealed a congenital transmesenteric defect through which loops of bowel had herniated and become gangrenous, resulting in resection and a stomy type Bouilly Volkmann.